Kustodiat za gospodarstvo, promet in transport - Sketelj, Polona (Etnolog. Nova vrsta (Ljubljana), 2003)
The article describes the development and activities of the Department of economy, traffic and transport of the Slovene Ethnographic Museum, taking account of the principal guidelines in the fields of ethnology and museology which had a major influence on the activities of the department in different periods. The article presents the department's collections, their classification, the methods of acquiring objects, and a view of its future development.
Keywords: Slovenski etnografski muzej; Ljubljana; economy; gospodarstvo; promet; kustodiati; muzejske zbirke